Digital technology as a tool to provide social support to individuals with cancer in low- and middle-income countries: A scoping review. - Hallie Dau; Fazila Kassam; Beth A Payne; Hana Miller; Gina Ogilvie (PLOS Digital Health)
Cancer is a rising cause of morbidity and mortality in low- and middle-income countries (LMICs). Individuals diagnosed with cancer in LMICs often have limited access to cancer prevention, diagnosis, and treatment services. Digital technologies, such as the Internet and mobile phones, could be used to provide support to individuals with cancer in a more accessible way. The goal of this scoping review is to understand how digital technology is being utilized by individuals with cancer for social support in LMICs. Four electronic databases were searched up to June 2024 to identify studies that reported on the use of digital technology for cancer social support in LMICs. Articles were included if they were published in English, included adults diagnosed with any type of cancer, and reported the use of digital technology for social support. Study characteristics, population demographics, and technological interventions reported were extracted. In all, 15 articles from 12 studies were included in the scoping review. Only four countries utilized digital technology for social support: China, Iran, Kenya, and Serbia. The most common cancer type reported was breast. Online health communities, Internet-based resources, mobile applications, and telecommunication were the four digital technologies reported. Overall, the articles demonstrated that the use of digital technology for social support can be beneficial for individuals diagnosed with cancer in LMICs. We found that digital technology may improve quality of life, reduce anxiety and depression, and allow individuals to connect with other individuals diagnosed with cancer. We concluded that there is a limited understanding of how digital technology can be used to support individuals with cancer in LMICs. Future research is needed to explore how digital technology can be utilized by underrepresented regions to offer avenues of support for regionally common cancer types such as cervical.